Engineering of the band gap induced by Ce surface enrichment in Ce-doped SnO2 nanocrystals - Pacheco-Salazar, D. G.; Aragon, F. F. H.; Villegas-Lelovsky, L. [UNESP]; Ortiz de Zevallos, A.; Marques, G. E.; Coaquira, J. A. H. (Elsevier B.V., 2020)
Surface modification of oxide semiconductors nanocrystals can promote news effects mainly in nanocrystals up to 10 nm in diameter. In these systems, the ratio surface/core is increased, and the quantum effect can not rule out. A form of tuning the crystallite size is by doping process. Our results showed a monotonic nanoparticle size decrease from similar to 10 to similar to 3 nm accompanied by the progressive Ce-enriched surface, with the volume of the unit cell increases as the Ce content is increased, evidencing solid-solution formation between the Sn and Ce ions in the rutile-type structure. The Fourier Transform Infrared spectroscopy measurements show a redshift of the Sn-O stretching vibration peak, which is in good agreement with the solid solution of Ce and Sn ions. The dopant enrichment of the nanocrystal surface, as evidenced by Raman spectroscopy is associated with a monotonic decrease of the PL intensity. The latter is induced by a progressive decreasing of the relative dielectric constant between the core and shell regions, which in turn is related to the narrowing of the optical band gap energy with increasing of Ce content. We attribute this effect to the enhancement of the surface polarization contribution that overtakes the confinement effect contribution.
Keywords: Nanocrystals; Ce doped SnO2; Solubility limit; Solid solution; Surface segregation; Optical band gap energy